Impact of Covid‐19 on dental hygiene educators: A national survey. Issue 7 (14th January 2022) - Arnett, Michelle C.; Ramaswamy, Vidya; Evans, Michael D.; Rulli, Danielle
Abstract: Purpose: The purpose of this study was to assess the impact of the Covid‐19 pandemic on dental hygiene (DH) educators' perception of personal and professional burnout and efficacy in the online/hybrid learning environment. Methods: A cross‐sectional study of DH faculty members from 327 United States entry level DH programs was invited to participate in this study. A 36 item survey was disseminated in Qualtrics xm March 2021. The Copenhagen Burnout Inventory was used to measure personal, work‐related, and burnout related to working with students. The Michigan Nurse Educators Sense of Efficacy for Online Teaching instrument was used to measure efficacy in online/hybrid learning. Results: The survey had an institutional response rate of 46%. Personal burnout scores had a significantly higher mean as compared to work‐related and burnout working with students' scores. A majority (66%) of respondents reported often feeling tired. Only personal burnout scores had a significant negative correlation with teaching efficacy scores. Administrators/program directors and full‐time faculty had significantly higher mean personal and work‐related burnout scores as compared to part‐time/adjunct clinical faculty. There were no significant differences in teaching efficacy scores by faculty position and institutional setting. Conclusion: COVID‐19 had significant impact on full‐time DH educators' personal and professional burnout levels. Full‐time administrators/program directors/DH educators reported higher levels of personal burnout. It seems that personal burnout has a negative relationship with teaching efficacy. Faculty position rather than institution impacted personal burnout. Despite personal and professional burnout, DH faculty reported low‐levels of burnout related to working with students.